Social Economy for Local Governance Structures: Monitoring and Evaluation Perspectives - Ioannis Nasioulas; George Tsobanoglou (European Regional Science Association (ERSA), 2006)
Social economy , the ground between free market private benefit institutions , the State regulation and society , needs to be positively identified. The existing , traditional , monitoring and evaluation concepts , methods and tools are prooven to ineffectively identify and describe the social conjunctions , adherent to the social mediation of the economic sphere. Coherent , scientifically valid , approaches need to be formulated. Up to date methods and tools , capable of reaching and describing the social economy phenomenon , emerge as a useful contribution , as long as they refrain from the traditional economistic and administrative context. The creation of a positive , new grammar for the identification of social economy forms the core of our interest. Local governance structures tend to lean upon such trends as they require partnership organizations to meet successfully local priorities essential to combat exclusion, poverty, acculturation, community growth and employability. Recent trends in the evaluation of this strategic field will be provided.
Keywords: 330